Revitalization of Islamic Education Curriculum: A Roadmap Towards Golden Indonesia 2045 - Ainal Mardhiah; Fadhilah; M. Chalis; Subhan; Nurlailan Kandi (Journal Informatic, Education and Management (JIEM), 2026)
The emergence of various local problems such as physical violence, psychological violence and sexual violence in very high numbers, in schools, at home, in educational institutions, in communities and in workplaces. There were 1,993 cases of violence against children and women recorded in 2024. In addition, the rampant corruption, use and distribution of drugs, marijuana, HIV / AIDS, LGBT. Abortion, free sex are serious challenges for the government. Coupled with global challenges such as war, the negative influence of modern technology requires Indonesia to think and choose the right and proven roadmap to realize a golden Indonesia in 2045. The Prophet Muhammad with the Qur'an has succeeded in bringing humans from the condition of ignorance that hurt each other, oppressed, killed, colonized to a life of mutual love. With the Qur'an, the Prophet Muhammad eliminated differences in social status, between the rich and the poor, between rulers and ordinary people, becoming equal before Allah SWT, except for those who are pious. With the guidance of the Qur'an and Hadith, Muslims have successfully mastered ¾ of the West. The Qur'an, Hadith, the sciences related to them, the sciences contained therein are the roadmap to a golden Indonesia in 2045. The Qur'an and Hadith are the solutions to the problems currently facing the Indonesian people, and the answers to the challenges of the global world, realizing a Golden Indonesia in 2045, by revitalizing Islamic education. Teach the Qur'an, Hadith, the sciences related to them, and the sciences contained therein in depth, completely, and thoroughly.